2016
DOI: 10.3329/jbcps.v34i1.29116
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Blood Transfusion Practices in Obstetrics and Gynecology in a Tertiary Hospital in Bangladesh

Abstract: Background: Blood transfusion is a life saving intervention in some obstetric and gynecological cases but is associated with risk of transfusion reaction and transmission of infection . Appropriate use of blood and blood products is of utmost importance for the safety of the patients. During the evaluation of an ongoing study on PPH,it appears that rate of blood transfusion is unexpectedly high in this centre, which raised the inquisitiveness in evaluating the rate and rationality of blood transfusion in prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 12 publications
2
14
1
Order By: Relevance
“…14 Also in another study it was seen that majority of patients 46.83% were recorded in hemoglobin range of 7-9 (g/dl). 12 Most of the patients (68.6%) in this study required blood and blood component transfusion because of obstetric hemorrhage where PPH (35.56%) was the most common indication. This was also seen in another study, where 70% patients admitted as obstetrical emergencies, required blood and its components transfusion due to obstetric hemorrhage and 30% required blood and its components transfusion due to severe anaemia.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…14 Also in another study it was seen that majority of patients 46.83% were recorded in hemoglobin range of 7-9 (g/dl). 12 Most of the patients (68.6%) in this study required blood and blood component transfusion because of obstetric hemorrhage where PPH (35.56%) was the most common indication. This was also seen in another study, where 70% patients admitted as obstetrical emergencies, required blood and its components transfusion due to obstetric hemorrhage and 30% required blood and its components transfusion due to severe anaemia.…”
Section: Discussionmentioning
confidence: 79%
“…11 Also in a study by Chowdhury F et al, done in Bangladesh, 68.3% of women were multiparous. 12 So, multiparity as such is a risk factor and these patients require utmost care in their management.…”
Section: Discussionmentioning
confidence: 99%
“…Chowdhury F et al have reported 9.2% of their patients who required transfusion. 9 In present study, were no transfusion reactions (BTRs) whereas in Madhushree D et al have reported 9 patients out of 204 who suffered from BTRs. 5 In present study, there was one maternal mortality of a multiparous patient who had delivered at home and developed septicaemia and DIC.…”
Section: Resultsmentioning
confidence: 43%
“…This is similar to study done by Chowdhary et al where the transfusion rate was 9.23% and common age group was from 21-30 years (76.58%). 9 Majority of transfusions were done for patients of gestational age 31-40 weeks (71.45%). Similar observation was made by Chawla S et al 10 In their study 23 (71.8%) women were in 31-40 weeks of pregnancy.…”
Section: Discussionmentioning
confidence: 99%